Pemanfaatan Pestisida Nabati Dalam Pengendalian Hama Tanaman Sayuran Di Desa Drono, Kabupaten Temanggung - Olivia Wardhani; Marisa Adilah Putri; Noval Hadad (PELITA NUSA TENGGARA, 2026)
Utilization of Botanical Pesticides in Controlling Vegetable Plant Pests in Drono Village, Temanggung Regency. The use of synthetic pesticides on vegetable crops is still a common practice among farmers because it is considered effective in controlling pests, but it has negative impacts on the environment and health. One environmentally friendly alternative is the use of botanical pesticides made from papaya leaves (Carica papaya L.) which contain bioactive compounds such as papain, alkaloids, flavonoids, terpenoids, and saponins. This community service activity aims to improve farmers' knowledge and skills in the manufacture and use of botanical pesticides as an effort to control aphid pests (Aphis gossypii Glover) on vegetable crops in Drono Village, Temanggung Regency. The method used is a participatory approach through the stages of observation, socialization and counseling, as well as demonstrations and direct practice. The activity evaluation was carried out using pre-test and post-test instruments for 33 participants covering six assessment aspects. The results of the activity showed an increase in the average knowledge score of participants from 32% in the pre-test to 86% in the post-test, representing an improvement of 54 percentage. In addition, most participants were able to follow and practice the stages of making botanical pesticides well.